Petrophysical evaluation and lithology delineation using cross-plots analysis from some onshore wells in the Nigerian-delta, west Africa - Ohakwere-Eze, Michael; Igboekwe, Magnus; Chukwu, Godswill (International Journal of Advanced Geosciences, 2018)
Reservoir rock attributes such as porosity, permeability, pore-size geometry and net-to-gross ratio can grossly be affected by inaccurate delineation of the sand intervals. It is therefore pertinent that well log cross-plot is utilized to accurately delineate the sand body and correctly evaluate the petrophysical properties of the mapped sandstone intervals. Three wells (A, B and C) were studied from which analysis of various cross-plots were done. The cross-plots of the density and gamma ray, Acoustic impedance and VpVs ratio with various colour indicators such vertical depth, porosity, resistivity, water saturation etc. were generated using the Hampson Russel software. The hydrocarbon interval in the area occurs between 5870ft to 8900ft for well-A, 5500ft to 5910ft for well-B and 5700ft to 7230ft for well-C as interpreted from the well logs with an average porosity range from 26 to 39%. Cross-plot analysis was carried out to validate the sensitivity of the rock attributes to reservoir saturation condition. The cross-plot results clusters shows two major lithologies of sandstone and shale with occasional intercalation of sand and shale units. For the three wells considered, ten reservoirs were observed. Fluid detection analysis shows that reservoirs A1-A2 (well-A), B1-B2 (well-B), C3-C4 (well-C) were found to contain oil, while reservoir A3-A4 (well-A) and C1-C2 (well-C) contains gas. This study has shown that the cross-plots approach can be used to accurately delineate reservoirs for further formation evaluation. It therefore means that an outright estimation of petrophysical properties on wrongly delineated reservoirs can signiï¬cantly affect the porosity, permeability, pore-size geometry and net-to-gross ratio of the reservoir units.